Honey as an inducer of phenolic compounds, flavonoids and growth of mango fruit var. ataúlfo - Albores-Flores, Victor Jesus (2024)
The production of honey has ancestral vestiges, considering Apis as the most domesticated and commercialized. On the other hand, meliponine bees, which have pre-Columbian remains, have been little studied and have important physicochemical properties of great value for use in agriculture. Mango cultivation, on which a variety of families depend for being a socioeconomic support, in addition to the above, is invested enough to sustain it with good agronomic management, where there are insufficient biological tools that allow for less harmful production to the environment. The objective of this work was to evaluate the eliciting action of defense metabolites and the growth induction of mango fruits when applying honey. The study was carried out at the San Juan ranch, in the municipality of Tapachula, Chiapas. Four treatments were established in the field, considering the production stages of the mango fruit. Significant differences were found between the concentrations of total phenols analyzed in the leaves and between all the treatments, observing that it is better to apply honey after flowering and during the growth of the mango fruit. No matter the concentration of honey used, both stimulate the growth of the mango fruit. A significant relationship was found between the concentrations of phenols, application time and growth of the mango fruit, with M. beecheii honey.